Enhancing Innovation and Creativity as Key Drivers of Organizational Culture among Private University Lecturers - Facmi Tamzil; Puspita Chairunnisa; Silvia Ratna Juwita (Majalah Ilmiah Bijak, 2025)
Private Higher Education Institutions (PTS) play a strategic role in developing superior human resources in Indonesia. However, the main challenge faced is the lack of integration of character values ​​and multiculturalism in the organizational culture of lecturers, which impacts weak academic innovation and creativity. To address this challenge, the government issued Permendikbud No. 12 of 2022 as a regulation emphasizing the importance of character development and multicultural education in higher education environments. This study aims to analyze the implementation of this regulation in developing an organizational culture for lecturers in PTS that supports a collaborative, innovative, and integrative work climate. The study used a descriptive qualitative approach with data collection techniques including in-depth interviews, observations, and documentation studies conducted at Esa Unggul University. Data were analyzed using thematic analysis using the Miles & Huberman model. The results show that the implementation of Permendikbud No. 12 of 2022 still faces obstacles such as resistance to change, low lecturer understanding, and limited structural and leadership support. However, character values ​​such as integrity and responsibility, as well as multicultural awareness, can act as catalysts for the formation of an organizational culture that encourages innovation and cross-cultural collaboration. An organizational culture built on a foundation of character values ​​and multiculturalism has been shown to increase lecturers' motivation, productivity, and adaptability in facing global dynamics. These findings provide strategic recommendations for private university leaders to strengthen transformative leadership, design ongoing training, and develop internal policies based on national regulations.